Syndromic surveillance and the reemergence of yellow fever in São Paulo state, Brazil, 2009 - Fortaleza, Carlos Magno Castelo Branco [UNESP] (2009)
Department of Tropical Diseases and Imaging Diagnosis Botucatu Medical School São Paulo State University, Botucatu, São Paulo State